Ciprofloxacin monoolein water gels as implants for the treatment of chronic osteomyelitis: In vitro characterization - Bavouma Charles Sombié; Josias Gérard Yameogo; Rasmané Semdé; Viviane Henschel; Karim Amighi; Jonathan Goole (Wolters Kluwer Medknow Publications, 2014)
This work investigated the possibility of using the biodegradable gentamicin-monoolein-water gels as models, in order to obtain a similar sustained release of ciprofloxacin hydrochloride. Four gels containing antibiotics were prepared and were examined with regard to their physicochemical properties and in vitro drug release characteristics. Ciprofloxacin, unlike gentamicin, which was dissolved in the matrix, was in dispersed form. However, despite its insolubility, microscopic observation, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and X-ray diffraction showed that the developed gel was in the cubic liquid crystalline structure and have maintained their ability to progressively release ciprofloxacin. ciprofloxacin-monoolein-water (5:80:15% w/w), which released in vitro approximately 85% of ciprofloxacin after 16 days could possibly be considered as an alternative to a gentamicin-monoolein-water gel for the treatment of chronic osteomyelitis.